2020
DOI: 10.1377/hlthaff.2020.00103
|View full text |Cite
|
Sign up to set email alerts
|

Return On Investment From Immunization Against 10 Pathogens In 94 Low- And Middle-Income Countries, 2011–30

Abstract: Estimating the value of global investment in immunization programs is critical to helping decision makers plan and mobilize immunization programs and allocate resources required to realize their full benefits. We estimated economic benefits using cost-of-illness and value-of-a-statistical-life approaches and combined this estimation with immunization program costs to derive the return on investment from immunization programs against ten pathogens for ninety-four low-and middle-income countries for the period 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 22 publications
1
53
0
Order By: Relevance
“…The full-immunization rate for children aged 12 to 23 months is as low as 50% in rural areas compared with 61% in urban areas [ 28 ]. The consequences of under-immunization of children in Uganda, as for other countries, include not only higher morbidity and mortality but also lost economic opportunity: Gavi, the Vaccine Alliance, has demonstrated that vaccination is integral to achieving 14 of the 17 SDGs, and the return on investment of immunization in Gavi-supported countries, when considering costs averted plus broader societal value, is $54 per every $1 spent [ 29 , 30 ].…”
Section: Local Settingmentioning
confidence: 99%
“…The full-immunization rate for children aged 12 to 23 months is as low as 50% in rural areas compared with 61% in urban areas [ 28 ]. The consequences of under-immunization of children in Uganda, as for other countries, include not only higher morbidity and mortality but also lost economic opportunity: Gavi, the Vaccine Alliance, has demonstrated that vaccination is integral to achieving 14 of the 17 SDGs, and the return on investment of immunization in Gavi-supported countries, when considering costs averted plus broader societal value, is $54 per every $1 spent [ 29 , 30 ].…”
Section: Local Settingmentioning
confidence: 99%
“…The total annual global deaths averted by vaccination go far beyond these estimates as only 98 countries were modeled, and deaths averted from polio, diphtheria, tetanus, pertussis, and from adult vaccinations were not modelled [ 10 ]. In a related modeling study it was estimated that from 2011 to 2030, immunization would avert $1510.4 billion (2018 USD; 95% CL $674.3–$2643.2) in costs of illness in 94 LMIC compared with no vaccination, and generate $3436.7 billion (95% CL $1615.8–$5657.2) in benefits [ 11 ], representing a return of $26.1 for every dollar invested using the cost-of-illness approach [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study by Sim et al. [1] is timely and strategic for current and future global public health planning. It justifies the decisions already made by several policy makers in different countries worldwide to invest in immunization programs against different diseases, which can also help to bring equity and diminish inequalities in a Global scale [ 6 , 7 ].…”
mentioning
confidence: 96%
“…For instance, the ROI can vary among the countries, according to diseases and periods of time. The ROI estimates from the study by Sim and colleagues [1] will inform and help country policy in funding the efforts to these programs and initiatives. However, the full benefits of an immunization programs will not only depend on sustained commitment and investment in these programs, but also on a better understanding of the immunization programs by the public that will support these decisions and actions.…”
mentioning
confidence: 99%
See 1 more Smart Citation